“Auditoría De Gestión a la Cooperativa de Ahorro y Crédito Andina Ltda. Agencia La Maná. Período Enero – Diciembre 2018”. - Zamora Herrera, Evelyn Carolina; Llanos García, Josselyn Gabriela (2020)
This research denominated Management Audit for the credit union “Andina Ltda”, La Maná branch office, January to December 2018 period, was carried out at this institution in La Maná. The main objective was to execute a Management Audit in this branch office during the period January - December 2018, which allows to verify the level of compliance with the goals and objectives set. The methodology used was a descriptive field research, supported by a documentary bibliographic investigation to provide the theoretical support of the research work. For the development of the audit, the 4 phases were carried out, each of them with their objectives and audit programs, the internal control questionnaire was prepared, which was applied to the personnel working in the different areas, with which the main flaws presented by the institution could be verified, as well as the risk and trust analysis in each of the Credit Union’s areas, where 89% confidence level and an 11% risk level were obtained; in the work papers the flaws found in each of the areas are detailed and in the sheet of findings, each of the weaknesses found is detailed, here they are detailed, the criteria, the causes, effects, conclusions and recommendations for each finding ; After completing all the phases, the presentation of the final report was made to the manager of the institution to take the necessary corrective measures.